2010
DOI: 10.1162/jocn.2009.21288
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Neural Effects of Long-term Stimulus–Reward Pairing in Macaque Visual Cortex

Abstract: It has been proposed that perceptual learning may occur through a reinforcement process, in which consistently pairing stimuli with reward is sufficient for learning. We tested whether stimulus-reward pairing is sufficient to increase the sensorial representation of a stimulus by recording local field potentials (LFPs) in macaque extrastriate area V4 with chronically implanted electrodes. Two oriented gratings were repeatedly presented; one was paired with a fluid reward, whereas no reward was given at any oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 49 publications
9
45
0
Order By: Relevance
“…4(a) reveals that the time interval during which a wave with a constant direction is present (around 50-100 ms after stimuli onset) corresponds to the early time interval of a prominent difference in average synchrony between the responses to the rewarded and unrewarded stimuli. This interval also corresponds to the one described in [14] and was attributed to sensorial learning in V4.…”
Section: Propagating Wavessupporting
confidence: 74%
See 3 more Smart Citations
“…4(a) reveals that the time interval during which a wave with a constant direction is present (around 50-100 ms after stimuli onset) corresponds to the early time interval of a prominent difference in average synchrony between the responses to the rewarded and unrewarded stimuli. This interval also corresponds to the one described in [14] and was attributed to sensorial learning in V4.…”
Section: Propagating Wavessupporting
confidence: 74%
“…When the signal of interest is large, fewer trials for averaging will be needed. As was shown in [14], which details the conditioning training of the experiment considered in this paper, an early neural response was observed that was suggested to be related to sensorial learning, and a later one to attentional learning. Based on this, temporal features are developed in this paper, and supplemented with a number of spatial features that serve as the input to the classifier whose aim is to distinguish the rewarded from the unrewarded stimulus responses.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Nonetheless, previous work found an enhanced and earlier N2pc-the ERP component used as an index of selective attention in the present study-when elicited by targets associated to the expectation of high rewards (Kiss et al, 2009). Animal electrophysiology is just beginning to explore modulations of visual processing that result from controlled stimulus-reward associations (Schuler and Bear, 2006;Peck et al, 2009;Frankó et al, 2010), but the exact link to the present findings is still unclear. Despite the recent surge of interest, and as noted in Introduction, the impact of reward on attention is not a prominent factor in models of visual search and attention (with the notable exception of Navalpakkam et al, 2009).…”
Section: Discussionmentioning
confidence: 86%